(untitled) (Communications in Computational Physics, 2020)
In this work, numerical simulations have been performed to study the shock/ droplet interaction before a standing wall. The research efforts are directed to reveal the influence of the reshock on the flow features and interfacial dynamics. A five-equation model is applied to model the compressible multi-fluid flow with moving interface. The governing equations are solved under an axisymmetric assumption using a finite volume method. By varying the incident shock Mach number (M_S) and the distance (L) between the droplet and the wall, the wave motion and the droplet deformation are closely examined for four typical simulations. Also, the underlying physics of some salient flow features and interfacial behavior is discussed. Moreover, the maximum wall pressure is monitored in term that structural damage is possibly induced to the wall as a result of the shock/droplet interaction. The droplet kinematics is examined via the center-of-mass displacement and velocity, to clarify the integral effects of changing M_S and L.